TREN PENGGUNAAN FLIPBOOK DALAM PENDIDIKAN: KAJIAN LITERATUR TERBARU - Dedy suhada; Santiani, Santiani (Cahaya Ilmu Bangsa Institute, 2025)
The development of digital technology has brought significant changes in the field of education, including in the use of instructional media. One increasingly utilized innovation is the flipbook, a digital interactive book that presents learning materials in a visual and engaging format. This article aims to explore the trends in the use of flipbooks in education through a literature review of previous studies. The findings show that flipbooks not only enhance students’ learning interest but also support independent learning, conceptual understanding, and active learner engagement in the learning process. Furthermore, this medium is considered effective across various educational levels and subjects, especially when combined with innovative teaching approaches. However, challenges still exist in its implementation, such as limited infrastructure and teachers’ digital literacy. Thus, flipbooks hold great potential in supporting a more interactive and enjoyable digital learning transformation.